2009
DOI: 10.1902/jop.2009.090249
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Regeneration by Transplantation of Periodontal Ligament Stem Cells and Bone Marrow Stem Cells in a Canine Peri‐Implant Defect Model: A Pilot Study

Abstract: This study demonstrated the feasibility of using stem cell-mediated bone regeneration to treat peri-implant defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 39 publications
4
153
0
3
Order By: Relevance
“…The differentiation of stem cells in osteoblasts may represent a breakthrough for tissue bioengineering. Studies have been demonstrating the DPSC potential to induce regeneration of critical-sized calvarial defects in mice (Moshaverinia et al 2014;Menicanin et al 2014); in canine and swine models, local implantation of DPSC, associated with β-TCP and HA/TCP scaffolds, successfully induced bone regeneration in critical-sized orofacial bone defects (Zheng et al 2009;Kim et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of stem cells in osteoblasts may represent a breakthrough for tissue bioengineering. Studies have been demonstrating the DPSC potential to induce regeneration of critical-sized calvarial defects in mice (Moshaverinia et al 2014;Menicanin et al 2014); in canine and swine models, local implantation of DPSC, associated with β-TCP and HA/TCP scaffolds, successfully induced bone regeneration in critical-sized orofacial bone defects (Zheng et al 2009;Kim et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, in another group using a canine peri-implant defect model, BMSC showed superior alveolar bone regeneration [40] . Furthermore, PDLSC microencapsulation in RGD-coupled alginate enhanced MSC viability, proliferation and osteogenic differentiation both in vitro and in vivo [41] .…”
Section: Pre-clinical Studiesmentioning
confidence: 92%
“…PDL regeneration was detected on titanium implant surfaces in a rat molar implant model [64]. When PDLSCs loaded HA/TCP were implanted in a canine saddlelike peri-implant defect model, newly formed bone was found to fill in defects [65]. In addition, one human clinical study has demonstrated cell-coated implant placement in the mandible and PDL formation around the implant surface.…”
Section: Periodontal Regenerationmentioning
confidence: 99%